The implementation of a new governance model for climate action: Two years after the enactment of the Framework Law on Climate Change in Chile - Moraga, Pilar (Revista de Derecho Ambiental, 2024)
The creation of a new institutional framework for climate change, responsible for the development, implementation, monitoring, reporting, and verification of climate change management instruments at the central and subnational levels, which enshrines the concrete actions to achieve the objectives and goals proposed by this new legal framework, by the commitments made in the Paris Agreement, installs a new governance model that lays the foundations to overcome the weaknesses existing up to that time.